Manipulating the local light emission in organic light-emitting diodes by using patterned self-assembled monolayers - Mathijssen, Simon G. J.; Hal, Paul A. van; Biggelaar, Ton J. M. van den; Smits, Edsger C. P.; Boer, Bert de; Kemerink, Martijn; Janssen, René A. J.; Leeuw, Dago M. de (Advanced materials, 2008)
Patterned organic light-emitting diodes are fabricated by using microcontact- printed self-assembled monolayers on a gold anode (see background figure). Molecules with dipole moments in opposite directions result in an increase or a decrease of the local work function (foreground picture), providing a direct handle on charge injection and enabling local modification of the light emission.